2022
DOI: 10.3389/fpsyg.2021.779594
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trend of Subjective Well-Being of Weibo Users During COVID-19: Online Text Analysis Based on Machine Learning Method

Abstract: Currently, the coronavirus disease 2019 (COVID-19) pandemic experienced by the international community has increased the usage frequency of borderless, highly personalized social media platforms of all age groups. Analyzing and modeling texts sent through social media online can reveal the characteristics of the psychological dynamic state and living conditions of social media users during the pandemic more extensively and comprehensively. This study selects the Sina Weibo platform, which is highly popular in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Web-based social media platforms can serve as e cient tools for tracking people's reactions to a series of news regarding a public event in a timely manner [ 8] .Thanks to the wide usage of social media, the online text database has become a "powerful tool" for the real-time monitoring of changes in an emotional state, SWB, and other psychological traits of its users. Sina Weibo is one of the major Chinese online social media in the Web 3.0 era and provides users with a platform for building social networks [ 9] .…”
Section: Introductionmentioning
confidence: 99%
“…Web-based social media platforms can serve as e cient tools for tracking people's reactions to a series of news regarding a public event in a timely manner [ 8] .Thanks to the wide usage of social media, the online text database has become a "powerful tool" for the real-time monitoring of changes in an emotional state, SWB, and other psychological traits of its users. Sina Weibo is one of the major Chinese online social media in the Web 3.0 era and provides users with a platform for building social networks [ 9] .…”
Section: Introductionmentioning
confidence: 99%
“…The psychology of ordinary people has also changed after the long-term development of the epidemic [ 21 ]. This kind of longitudinal research that emphasizes “temporal dynamic trends” is rare in previous studies [ 22 ]. Because of the discovery of these complex issues, it is currently unclear how the impact of epidemic policies will evolve over time, which may be related to specific influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most popular social media platforms in China, Sina Weibo (Weibo) has aggregated huge numbers of sadness, fear, anger or happy texts about some hot issues (Sina Weibo Data Center, 2021 ; Zhang & Yu, 2018 ). Mining and exploring this kind of massive data from social media is of great significance to the correct and objective understanding of the emotions and attitudes of netizens, and to studying the emotional expression of individuals in the network environment (Han et al, 2022 ). Meanwhile, it can also provide theoretical reference for government departments to recognize and guide trends related to public opinion evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Salathé and Khandelwal ( 2011 ) investigated the emotional expression of Twitter users during the H1N1 pandemic and found that the emotional intensity of Twitter users showed the characteristics of temporal and spatial changes with the development of the H1N1 pandemic (Salathé & Khandelwal, 2011 ). In general, while sentiment analysis has become a mainstream research method for studying individual emotional expression (Feng et al, 2020 ; Kirelli & Arslankaya, 2020 ), the use of NLP technology to analyze the emotional expression of users in public health emergencies has also been proven feasible (Han et al, 2022 ; You et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation